A metaphorical analysis of The Love Song of J. Alfred Prufrock by T. S. Eliot. Issue 1 (March 2018) - Brown, Alistair
Abstract: Using the theory of conceptualisation of metaphor, this study analyses the imagery created by accounting metaphors of The Love Song of J. Alfred Prufrock. The paper applies a typology of metaphors as the basis of metaphorical analysis for the detection of accounting in Eliot's poem. The results of the study suggest that the poem relies on accounting metaphors that use either unstated vehicle concepts, unstated tenor concepts or both to convey dense messages of accounting. An implication arising from the results is that considerable transfers of meaning from one epistemic element to another are needed to unlock Eliot's accounting messages.